Native games indigenous peoples and sports in the post-colonial world - Hallinan, Chris; Judd, Barry (Bingley, U.K. : Emerald, 2013)
Research on Indigenous participation in sport offers many oppertunities to better understand the political issues of equality, empowerment, self-determination and protection of culture and identity. This volume compares and conceptualises the sociological significance of Indigenous sports in different international contexts. The contributions, all written by Indigenous scholars and those working directly in Indigenous/Native Studies units, provide unique studies of contemporary experiences of Indigenous sports participation. The papers investigate current understandings of Indigeneity found to circulate throughout sports, sports organisations and Indigenous communities. by (1): situating attitudes to racial and cultural difference within the broader sociological processes of post colonial Indigenous worlds (2): interrogating perceptions of Indigenous identity with reference to contemporary theories of identity drawn from Indigenous Studies and (3): providing insight to increased Indigenous participation, empowerment and personal development through sport with reference to sociological theory.
Introduction / Chris Hallinan, Barry Judd -- No 'museum piece' : aboriginal games and cultural contestation in subarctic Canada / Michael K. Heine -- Lassoing and reindeer racing versus 'universal' sports : various routes to Sámi identity through sports / Eivind ô. Skille -- 'A reservation hero is a hero forever' : basketball, irony, and humor in the novels of James Welch, Sherman Alexie, and Stephen Graham Jones / Billy J. Stratton -- Neoliberalism as neocolonialism? : Considerations on the marketisation of Waka Ama in Aotearoa/New Zealand / Renee K.L. Wikaire, Joshua I. Newman -- Towards cultural competence : how incorporating Maori values could benefit New Zealand sport / Holly Raima Hippolite, Toni Bruce -- Resisting critical analyses : gatekeeping issues with Australian indigenous subjects / Stella Coram, Chris Hallinan -- Sport for development in Zambia : the new or not so new colonisation? / Ruth Jeanes ... [et al.] -- The legacy of Jack Johnson on aboriginal Australia / John Maynard -- Indigenous reconciliation games : selling Australian football as the new game to the new South Africa / Barry Judd, Chris Hallinan -- Youth development through recreation : Eurocentric influences and aboriginal self-determination / Alana Rovito, Audrey R. Giles -- Paradigm lost : indigenous games and neoliberalism in the South African context / Cora Burnett -- Hope and strength(s) through physical activity for Canada's aboriginal peoples / Victoria Paraschak -- Uncomfortable icons : uneasiness, expectations, and American Indians in sport / C.Richard King.
Print version record
Keywords: Indigenous peoples -- Sports; Indigenous peoples -- Political and social views; Indigenous peoples -- Social life and customs; Sports & Recreation -- Sociology of Sports; Social Science -- Ethnic Studies -- General; Sociology: sport & leisure; Olympic games